SOSIALISASI MEMBANGUN KOPERASI DALAM MENDUKUNG PEREKONOMIAN MASYARAKAT DESA PURBA DOLOK SANGGUL KABUPATEN HUMBANG HASUNDUTAN - Donna Maryati Panggabean; Dahlia Nopelina Siallagan; Hotlin Siregar; Niarita Bukit (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2022)
This community service is carried out with the topic of building cooperatives in supporting the economy of rural communities. Dolok Purba Village has a very potential area in the agricultural sector. The village of Purba Dolok also has a cooperative that is able to accommodate agricultural products from the village community and act as a facilitator for agricultural needs. However, the cooperative's activities have not been going well because the processing system is not optimal. For this reason, the presenters were very interested in doing community service on the topic